Nine chapters on mathematical modernity: essays on the global historical entanglements of the science of cumbers in China - Bréard, Andrea (Springer, 2019)
1 Visions of Antiquity -- 2 The Ellipse Seen from 19th Century China -- 3 Filling Euclid’s Gaps -- 4 Negotiating a Linguistic Space in-between -- 5 Discourse Transformed: Changing Modes of Argumentation -- 6 Fate Calculation : The Mathematics of Divination -- 7 Data Management and Knowledge Production in Late Qing Institutions -- 8 Data Management and Knowledge Production in Late Qing Institutions -- 9 Visions of Modernity
Keywords: Geschichte 1800-1950; China